2015
DOI: 10.1160/th15-04-0325
|View full text |Cite
|
Sign up to set email alerts
|

High levels of TSP1+/CD142+ platelet-derived microparticles characterise young patients with high cardiovascular risk and subclinical atherosclerosis

Abstract: Circulating microparticles (cMPs) play important roles in cellular crosstalk and are messengers of cell activation. We have previously reported that platelet-released microparticles (pMPs) stimulate thrombosis and that lipid-lowering treatment as per guidelines in patients with familial hypercholesterolaemia (FH) is not sufficiently effective in reducing pro-inflammatory cell activation and, consequently, CD45+/CD3+-lymphocyte-derived cMP shedding. FH patients, due to life-long vascular exposure to high LDL-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 50 publications
0
63
0
2
Order By: Relevance
“…Along with numerous studies, it has been proved that the number and content of EVs could differ depending on the state of the disease making them potential candidates for non‐invasive biomarkers. Indeed, increased levels of circulating EVs have been reported in CVDs …”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%
“…Along with numerous studies, it has been proved that the number and content of EVs could differ depending on the state of the disease making them potential candidates for non‐invasive biomarkers. Indeed, increased levels of circulating EVs have been reported in CVDs …”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%
“…Erosion, fissure, or rupture of the atherosclerotic plaques are triggering events in ACS, being platelets a key player in these atherothrombotic processes (Fuster et al, 1990). We have found that HCVR patients have significantly high shedding of cMVs carrying epitopes of platelet activation and directly associate to lipid-rich subclinical atherosclerotic burden (Suades et al, 2015a). Besides, these prothrombotic pMVs have demonstrated an incremental prognostic value beyond the classical risk factor model for the prediction of cardiovascular risk, indicating that the state of activation of platelets in the blood-vascular interface may increase the release of pMVs that become markers of the high atherothrombotic risk (Suades et al, 2015a).…”
Section: Platelet-derived Microvesicles In Atheroinflammation and Athmentioning
confidence: 99%
“…We have found that HCVR patients have significantly high shedding of cMVs carrying epitopes of platelet activation and directly associate to lipid-rich subclinical atherosclerotic burden (Suades et al, 2015a). Besides, these prothrombotic pMVs have demonstrated an incremental prognostic value beyond the classical risk factor model for the prediction of cardiovascular risk, indicating that the state of activation of platelets in the blood-vascular interface may increase the release of pMVs that become markers of the high atherothrombotic risk (Suades et al, 2015a). Blood thrombogenicity can be partially explained by the fact that TF is not only present in the subendothelium, but also in the circulation (Sambola et al, 2003).…”
Section: Platelet-derived Microvesicles In Atheroinflammation and Athmentioning
confidence: 99%
“…Therefore, increased level of circulating platelet-derived MPs was found in older age individuals without CV disease, as well as in the younger individuals with high CV risk due to subclinical atherosclerosis [96] and patients with known CV diseases [97]. However, the fractions of platelet-derived MPs expressed P-selectin or CD63 were higher in the patients with peripheral arterial disease and ST-segment elevation myocardial infarction [97] that confirmed the role of activated platelets-derived MPs in the pathogenesis of thrombus formation and platelet aggregations [98].…”
Section: Platelet-derived Mpsmentioning
confidence: 99%
“…Although the importance of platelet-derived MPs in the pathogenesis of CV diseases is still debated [93][94][95][96], there are data regarding directly effect of platelet-derived MPs on formation of foam cells in atherosclerotic plaque [97]. Therefore, increased level of circulating platelet-derived MPs was found in older age individuals without CV disease, as well as in the younger individuals with high CV risk due to subclinical atherosclerosis [96] and patients with known CV diseases [97].…”
Section: Platelet-derived Mpsmentioning
confidence: 99%